The effectiveness of project based learning with creative mind-map tasks for improving mathematical connection ability and student curiosity - Kartika, Yudha Kristia; Pujiastuti, Emi; Soedjoko, Edy (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aimed to know the effectiveness of PjBL learning model with creative mind-map assignments on student’s Mathematical Connection Abilities and student’s curiosity. Population in this study was students of grade VIII SMP Negeri 1 Margorejo Pati year 2017/2018 with a true experimental design types posttest-only control design and samples were chosen randomly. Analysis of data used the proportion test and t-test. The results showed that (1) the ability of student’s mathematical connection of the subject who have gained PjBL learning model with creative mind-map assignments have achieved the classical completeness; (2) the mathematical connection abilities of students who have gained PjBL learning model with creative mind-map assignments is higher than students who have gained expository models and (3) the curiosity of students who have gained PjBL learning model with creative mind-map assignments is higher than students who have gained expository models.